The effects of structural adjustment on deforestation and forest degradation in lowland Bolivia - Kaimowitz, D.; Thiele, Graham; Pacheco, P. (1999)
Bolivia's structural adjustment policies, initiated in 1985, increased poverty among certain groups, but this did not lead to widespread migration to the agricultural frontier. Nor did adjustment greatly affect the average area planted in annual crops by small lowland farmers. Structural adjustment contributed to large-scale forest clearing for soybean production for export and, to a lesser extent, forest degradation by lumber companies. The economic benefits generated by soybean and timber expansion may have outweighed the environmental costs, but alternative policies might have reduced those costs and improved the distribution of the benefits.